Effectiveness of PK-Guided Personalized Recombinant FVIII Treatment in Patients with Hemophilia A: Clinical Case Experiences Based on an Observational Study - Mizoguchi Y; Hino M; Ueda H; Miyaguchi Y; Kobayashi M (Journal of Blood Medicine)
Yoko Mizoguchi,1 Moeko Hino,2 Hitoshi Ueda,3 Yasuo Miyaguchi,3 Masao Kobayashi1,4 1Department of Pediatrics, Hiroshima University Graduate School of Biomedical Sciences, Hiroshima, Japan; 2Department of Pediatrics, Chiba University Hospital, Chiba, Japan; 3Japan Medical Office, Takeda Pharmaceutical Company Limited, Tokyo, Japan; 4Japanese Red Cross, Chugoku-Shikoku Block Blood Center, Hiroshima, JapanCorrespondence: Yasuo Miyaguchi, Japan Medical Office, Takeda Pharmaceutical Company Limited, 2 Chome-1-1 Nihonbashihoncho, Chuo-ku, Tokyo, 103-0023, Japan, Tel +81 70-4921-7966, Email yasuo.miyaguchi1@takeda.comPurpose: Prophylaxis with recombinant factor VIII (rFVIII) products is the gold-standard treatment for hemophilia A. However, interindividual differences affect the half-life and clearance of rFVIII products. The myPKFiT is a web-based medical-device software program for population pharmacokinetic (PK) simulation of FVIII products to guide accurate FVIII doses and dosing intervals. In this Japanese multicenter observational study, the efficacy of regimen adjustment using myPKFiT was examined.Patients and Methods: Male patients with hemophilia A undergoing personalized treatment with myPKFiT using either octocog alfa or rurioctocog alfa pegol were included. Patients were aged < 18 years. Primary endpoint was annualized bleeding rate (ABR). Secondary endpoints were ABR by type of bleeding, rFVIII product consumption, physical activity level, quality of life, and frequency of rFVIII administrations. Results are presented descriptively; however, for exploratory analysis, data before and after regimen adjustment were compared using the Wilcoxon signed-rank test.Results: Seven patients aged 3– 17 years (median age 13 years) participated in the study. Mean ABR for all bleeds decreased by 0.86 after PK-guided regimen adjustment. Four patients showed zero ABR before and after regimen adjustment using myPKFiT. No significant differences were noted in the consumption of rFVIII products. However, mean rFVIII consumption decreased in two patients after PK-guided regimen adjustment. Three patients increased physical activity and, according to the treatment based on the PK-guided regimen adjustment, this resulted in no increased bleeding.Conclusion: The results from this study in a small number of patients suggest that PK-guided regimen adjustment with myPKFiT may support optimization of the individual prophylactic administration of the FVIII products octocog alfa and rurioctocog alfa pegol.Study Registration: UMIN000044800.Keywords: annual bleeding rate, myPKFiT, prophylaxis, pharmacokinetic adjustment